Effects of essential oil of Origanum onites and its major component carvacrol on the expression of toxicity pathway genes in HepG2 cells - Özlem Tomsuk; Victor Kuete; Hülya Sivas; Mine Kürkçüoğlu (BMC, 2024)
Abstract Background Origanum species have been used in various commercial constructions as a remedy against burns and wounds, agriculture, alcoholic drinks, fragrance, and flavoring substances of food products. The essential oil of Origanum onites L. (EOOO) and its component carvacrol (CV) possesses a wide range of biological activities including anti-cancer activity. Purpose The purpose of this study was to investigate the growth inhibitory activity of the essential oil and its major component CV and then hepatotoxicity pathway-related genes in HepG2 cells. Methods The effects of the EOOO and CV on cell growth and mRNA expressions of 84 hepatotoxicity pathway-related genes were investigated in HepG2, using trypan blue exclusion/ bromodeoxyuridine (BrdU) incorporation tests and real-time-polymerase chain reaction (RT-PCR) array, respectively. Results The EOOO and CV inhibited cell growth with IC50 values of 0.08 µg/mL and 45 µg/mL, respectively, after 24 h. Real-time, reverse-transcription-polymerase chain reaction (RT2-PCR) array analysis revealed that expressions of 32 genes out of 84 were changed at least 2-fold or more in the EOOO-treated cells. Among them, expression levels of 17 genes were elevated, while expression levels of 15 genes were diminished. Furthermore, after exposure of cells to 45 µg/mL of CV, the expression of 8 genes was increased while the other 8 genes were decreased. Both the EOOO and carvacrol affected the expression of 48 genes of HepG2 cells which are involved in the hepatotoxicity pathway, indicating their hepatoprotective and possible anti-hepatocarcinogenic effects. Conclusion The present study demonstrates that the essential oil of Origanum onites and carvacrol can be used in various applications such as anticancer or herbal drugs, since its non-hepatotoxicity.